IMPROVING KNOWLEDGE AND ATTITUDES ABOUT CERVICAL CANCER DETECTION IN JAVA'S PANTURA REGION: PENINGKATAN PENGETAHUAN DAN SIKAP TENTANG DETEKSI KANKER SERVIKS DI PANTURA PULAU JAWA - Rahmanto, Ilham; Hanum, Safa Salsabila; Safitri, Cahyani Tiara; Khaerana, A. Insyirah; Targanski, Constantia Lidwina; Hendrarto, Bagus Adjie Dwi; Hartawan, M. Wildan Nabalah; Susilo, Imam (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Early detection of cervical cancer through IVA and Pap smear examination is crucial for preventing and reducing cervical cancer mortality. However, IVA and Pap smear coverage in Indonesia, particularly in Mentaras Village, Gresik Regency, remains low. The low knowledge and attitudes of women of childbearing age towards IVA and Pap smear examinations are major obstacles to early detection. Objective: This community service aims to improve the knowledge and attitudes of women of childbearing age in Mentaras Village towards IVA and Pap smear examinations through health socialization. Method: Health socialization was conducted for 23 participants from the PKK mothers' group using PowerPoint presentations and brochures. Evaluation was performed using a post-test questionnaire to measure participants' knowledge and attitudes after the activity. Results: After the socialization, all participants (100%) demonstrated a good level of knowledge, and 91.30% showed a positive attitude towards IVA and Pap smear examinations. These results indicate that the socialization activity positively impacted participants' awareness. Conclusion: Health socialization effectively improved understanding and attitudes towards the early detection of cervical cancer. Regular similar activities are recommended to expand community participation.